2006
DOI: 10.1299/jsmea.49.411
|View full text |Cite
|
Sign up to set email alerts
|

Study on Thickness Effect of Three-Point-Bend Specimen

Abstract: The thickness effect of a three-point-bend (3PB) specimen on dimple fracture behavior is studied experimentally and numerically. At first, fracture toughness tests were conducted using 3PB specimens of different thicknesses. Fracture toughness values and R-curves are obtained, and the thickness effect is discussed. Using scanning electron microscopy (SEM), dimple fracture surfaces are observed precisely. It is found that the thickness effect appears clearly in the void growth process. Finite element (FEM) anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Cortical bone thickness exhibited the greatest association with failure load in the same study. It has also been reported that dimple fracture is affected by bone thickness (97). This highlights the significance of the three-point bending test result that administration of C. siliqua significantly increased the thickness index compared to the OVX group for the right femur, even though it remained significantly lower compared to the control group when the index was examined regardless of the foot factor.…”
Section: Discussionsupporting
confidence: 52%
“…Cortical bone thickness exhibited the greatest association with failure load in the same study. It has also been reported that dimple fracture is affected by bone thickness (97). This highlights the significance of the three-point bending test result that administration of C. siliqua significantly increased the thickness index compared to the OVX group for the right femur, even though it remained significantly lower compared to the control group when the index was examined regardless of the foot factor.…”
Section: Discussionsupporting
confidence: 52%